Genealogies of Testimony in Post-Dictatorship Argentine Literature: María Negroni’s La Anunciación - Venturini, Ximena (Escritura e Imagen, 2024)
The article carries out a genealogy of the testimonial genre based on an analysis of the novel La Anunciación by the Argentine writer María Negroni. Some of Longoni’s (2007) ideas on the testimonial genre in contemporary Argentina and the suspicion that fell under the survivors will be applied, as well as the concept of “threshold” coined by Forcinito (2012). On the other hand, the testimonial genre will be studied in relation to the phenomena of the tension between mourning and narration that Avelar (1999) identified in post-dictatorship literatures in the Southern Cone. These ideas will be applied to the novel analyzed in this paper.